Analisis Pengaruh Return on Asset, Gross Profit Margin Terhadap Capital Structure dengan Firm Size Sebagai Variabel Moderasi - Novita Sundari; Andre Prasetya Willim (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to determine the effect of Return of Asset, Gross Profit Margin on Capital Structure with Firm Size as the moderate variabel in properties and real estates sector companies listed on Indonesia Stock Exchange for the 2020-2024 period. Sample was conducted using a purposive sampling method to select 52 of the 92 properties and real estates companies sampled in the study. The findings of this study indicate that Capital Structure is positively influenced by Gross Profit Margin, but not by Return on Asset. Although Firm Size is able to moderate the effect of Gross Profit Margin on Capital Structure, it cannot reduce the effect of return on asset.